Work related characteristics, work-home and home-work interference and burnout among primary healthcare physicians: A gender perspective in a Serbian context - Houkes Inge; Putnik Katarina (BMC, 2011)
Abstract Background Little information exists on work and stress related health of medical doctors in non-EU countries. Filling this knowledge gap is needed to uncover the needs of this target population and to provide information on comparability of health related phenomena such as burnout across countries. This study examined work related characteristics, work-home and home-work interference and burnout among Serbian primary healthcare physicians (PHPs) and compared burnout levels with other medical doctors in EU countries. Methods Data were collected via surveys which contained Maslach Burnout Inventory and other validated instruments measuring work and home related characteristics. The sample consisted of 373 PHPs working in 12 primary healthcare centres. Data were analysed using t-tests and Chi square tests. Results No gender differences were detected on mean scores of variables among Serbian physicians, who experience high levels of personal accomplishment, workload, job control and social support, medium to high levels of emotional exhaustion, medium levels of depersonalisation and work-home interference, and low levels of home-work interference. There were more women than men who experienced low job control and high depersonalisation. Serbian physicians experienced significantly higher emotional exhaustion and lower depersonalisation than physicians in some other European countries. Conclusions To diminish excessive workload, the number of physicians working in primary healthcare centres in Serbia should be increased. Considering that differences between countries were detected on all burnout subcomponents, work-related interventions for employees should be country specific. The role of gender needs to be closely examined in future studies as well.